2003
DOI: 10.1007/s00122-003-1509-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.)

Abstract: Low-temperature germination is one of the major determinants for stable stand establishment in the direct seeding method in temperate regions, and at high altitudes of tropical regions. Quantitative trait loci (QTLs) controlling low-temperature germinability in rice were identified using 122 backcross inbred lines (BILs) derived from a cross between temperate japonica varieties, Italica Livorno and Hayamasari. The germination rate at 15 degrees C was measured to represent low-temperature germination and used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
228
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(239 citation statements)
references
References 23 publications
6
228
0
5
Order By: Relevance
“…Further analysis will be required to prove the allelic relationship between these QTLs. Also, the qltg4 QTL detected in this study appears to be the same as those identified in the japonica/indica population (Miura et al, 2001) and japonica/japonica population (Fujino et al, 2004). However, the allelic rela- …”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Further analysis will be required to prove the allelic relationship between these QTLs. Also, the qltg4 QTL detected in this study appears to be the same as those identified in the japonica/indica population (Miura et al, 2001) and japonica/japonica population (Fujino et al, 2004). However, the allelic rela- …”
Section: Discussionsupporting
confidence: 74%
“…Three QTLs for low-temperature germination have been identified by studies of crosses between temperate japonica Italica Livorno and Hayamasari (Fujino et al, 2004). One QTL, qLTG-3-1 near the marker GBR3001 was located on chromosome 3, and the Italica Livorno allele in this QTL increased low temperature germination (Fujino et al, 2004). Based on the chromosomal location, this QTL appears to correspond to the qltg3 detected in this study.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations